Graduated Exposure and Positive Reinforcement to Overcome Setting and Activity Avoidance in an Adolescent With Autism. (January 2013) - Schmidt, Jonathan D.; Luiselli, James K.; Rue, Hanna; Whalley, Katherine
Some students who have developmental disabilities avoid settings and activities that can improve their learning and quality of life. This two-phase study concerned an adolescent boy with autism who avoided the gross-motor exercise room, gymnasium, and music room at his school; he demonstrated distress, agitation, and problem behaviors when prompted to enter these areas. Using graduated exposure combined with positive reinforcement, he learned to enter these settings without resisting and eventually to participate in activities within the settings. This article discusses this intervention approach for reducing and eliminating avoidant behavior.